Development of Mathematics Learning Devices with GDL Models to Improve Mathematical Problem-Solving Ability of Class VII Junior High School - Efni, Latifa; Yerizon Yerizon; Zusti Jamaan, Elita (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to produce mathematics learning tools with the Guided Discovery Learning (GDL) Model which is Valid, practical, and effective to improve the mathematical problem-solving abilities of students in class VII SMP/MTsN. The Plomp model is used because it is more flexible than Plomp's other models; beside that, at each step, it contains activities development that can be adapted to the characteristics of the research. Instruments were used during the study in the form of observation sheets, interview guidelines, questionnaires, validation sheets, learning tools, and tests of mathematical problem-solving skills learners. The results of the validity test show that the GDL-based mathematics learning tool is declared valid according to the experts. The results of the practicality test show that GDL-based mathematics learning tools are practical based on teachers and students as users. The effectiveness test results show that students' learning outcomes after learning are better by showing the percentage of completeness that reaches 75.86% exceeding the specified effectiveness limit of 70%. In addition, the device is said to be effective; it can be seen from the activities of students during the learning process that it has increased. Based on the validity, practicality, and effectiveness tests, the mathematics learning tools based on GDL in the Association material for Class VII Junior High School students are valid, practical, and effective